Survey on Training Adequacy for IV Infusion and Titration Calculations among Nurses and Interns (International Journal of Scientific Research in Science and Technology, 2025)
Background: Accurate intravenous (IV) infusion rate setting and titration are critical for patient safety, particularly in acute care settings. Errors in IV drug administration often stem from inadequate training in dose calculation and infusion adjustments, which can lead to subtherapeutic effects or toxicities. Objective: To assess the adequacy of training and identify gaps in knowledge related to IV infusion and titration calculations among nursing staff and pharmacy/medical interns. Methodology: A cross-sectional, questionnaire-based survey was conducted among 40 participants comprising nurses and interns from medical and pharmacy backgrounds. The survey included questions assessing knowledge of infusion rate calculations, titration principles, familiarity with infusion devices, and confidence in managing patient-specific scenarios requiring dose adjustments. Results: Most participants were aware of titration protocols and could perform basic infusion rate calculations, but many struggled with complex titration problems. Infusion pump use was linked to higher accuracy. Over half had witnessed or made IV infusion errors, with lack of training as the main cause. Hands-on workshops and simulation-based learning were the most preferred training methods. Conclusion: The study highlights the urgent need for structured, competency-based training in IV infusion and titration practices. Incorporating simulation, technology-assisted learning, and regular assessments into professional education can improve accuracy, reduce errors, and enhance patient safety.